การแสวงหาและการใช้สารสนเทศของผู้ปฏิบัติการพยาบาลขั้นสูง(Information-seeking and Information Use of Advanced Practice Nurse) - (Phattaranitch Surakomolsedth), ภัทรนิษฐ์ สุรโกมลเศรษฐ์; (Dr.Malee Kabmala), ดร.มาลี กาบมาลา (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาการแสวงหาและการใช้สารสนเทศของอาจารย์พยาบาลและ พยาบาลผู้ปฏิบัติการพยาบาลขั้นสูง โดยจะนำไปใช้เป็นแนวทางการศึกษาความรู้ความสามารถของนักสารสนเทศ ในกระบวนการพยาบาลตามหลักฐานเชิงประจักษ์ เนื่องจากการปฏิบัติทางการพยาบาลให้มีคุณภาพ จำเป็น ต้องใช้สารสนเทศที่มีความทันสมัย ถูกต้อง และน่าเชื่อถือ มาใช้ในการปฏิบัติงานให้เกิดประโยชน์สูงสุด โดยความต้องการใช้สารสนเทศของผู้ใช้ สามารถส่งผลต่อความรู้ความสามารถของนักสารสนเทศผู้ให้บริการ เนื่องจากต้องจัดบริการสารสนเทศที่เหมาะสมกับความต้องการของผู้ใช้กลุ่มดังกล่าว ผู้วิจัยจึงได้ทำการศึกษา การแสวงหาและการใช้สารสนเทศของอาจารย์พยาบาลและพยาบาลผู้ปฏิบัติการพยาบาลขั้นสูง โดยมีกลุ่ม ตัวอย่างในการศึกษา จำนวน 405 คน ประกอบด้วย อาจารย์พยาบาล จำนวน 89 คน และพยาบาลผู้ปฏิบัติการ พยาบาลขั้นสูง จำนวน 316 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล คือ แบบสอบถาม และได้รับกลับ คืนมา จำนวน 290 ชุด คิดเป็น ร้อยละ 71.60 วิเคราะห์ข้อมูลด้วยค่าสถิติร้อยละ ผลการวิจัยพบว่า 1) การ แสวงหาสารสนเทศทางการพยาบาลของอาจารย์พยาบาลและพยาบาลผู้ปฎิบัติการพยาบาลขั้นสูง ส่วนใหญ่ใช้ แหล่งสารสนเทศอินเตอร์เน็ตมากที่สุด และมีความรู้ความสามารถในการใช้คอมพิวเตอร์และอินเตอร์เน็ต ในการสืบค้นข้อมูลในระดับใช้ได้ดีจนถึงเชี่ยวชาญ ทำการสืบค้นสารสนเทศด้วยตนเองทุกครั้ง การดำเนิน การแสวงหาสารสนเทศอย่างมีขั้นตอน มีกลยุทธ์สำคัญที่ใช้ในการสืบค้น คือ คำสำคัญ ในการสืบค้นทุกครั้ง บางครั้งใช้หัวเรื่องและศัพท์เฉพาะทางการพยาบาลในการสืบค้น และใช้ฐานข้อมูลออนไลน์เพื่อการสืบค้น สารสนเทศ โดยส่วนใหญ่ใช้ฐานข้อมูลทางด้านการแพทย์และการพยาบาลในระดับมาก และสารสนเทศที่สืบค้น ได้ตรงกับความต้องการทุกครั้ง แต่บางครั้งมีปริมาณไม่เพียงพอ และใช้บริการยืมระหว่างห้องสมุดมากที่สุด 2) การใช้สารสนเทศทางการพยาบาลส่วนใหญ่มีวัตถุประสงค์เพื่อค้นคว้าวิจัย การจัดการทางการพยาบาล เพิ่มพูนความรู้และจัดเตรียมการเรียนการสอนทางการพยาบาล ประเภทของสารสนเทศที่ใช้ มากที่สุด คือ บทความวิชาการจากวารสารทางการพยาบาล และรายงานการทบทวนงานวิจัย ความถี่ในการใช้เดือนละ 2 – 3 ครั้ง ลักษณะสารสนเทศที่ใช้เป็นงานวิจัยแบบ Systematic Review และแบบ Randomized Controlled Trials มากที่สุด 3) ปัญหาการใช้สารสนเทศทางการพยาบาล ส่วนใหญ่ปัญหาที่พบ คือ ปัญหา ด้านเวลา เนื่องจากมีภาระงานประจำเป็นจำนวนมากทำให้ไม่มีเวลาในการสืบค้นสารสนเทศ This study aims to explore the information seeking and information use of nurse lecturers and advanced practice nurses which are parts of the learning of information specialists as shown with empirical evidence in the nursing procedures. The quality of nursing practice were required an accurate, complete and reliable of information. The information needs of users affect to the ability of an information provider that have to providean appropriate service for nurse lecturers and advanced practice nurses. The sample in the study consists of 405 participants including 89 nurse lecturers and 316 advanced practice nurse. To collect the data, the questionnaire was used. A total of returned questionnaire was 290, representing 71.60 percent of all distributed questionnaire. To analyze the data, the percentage was employed. The results showed three key implications as follows; 1) The information seeking of nurse lecturers and advanced practice nurses is implemented by the internet as the most selected source. Their knowledge and skills required to use computers and the internet for searching information are ranked at the high to expertise level. They searched the information by themselves, following the sequential searching steps. A key strategy to search any information is to use to keywords. In addition, subject and technical terms can be employed. Moreover, online database is exploited, especially in the context of medical and nursing that has been using at the high level. The anticipated and actual gained information are mostly consistent. However, the number of information is limited. Furthermore, lending service is used at the highest level. 2) The information use is mainly purposed to conduct research regarding nursing management, expand knowledge and prepare for the lecture. The most used types of information are scholarly articles from the journal of nursing and reviews of research reports. Frequency of use is between two to three times per month. Those most used types of the study are systematic review and randomized controlled trials research. 3) The issue found in the information use is concerned with the time constraint. Due to the work load of the salary workers, spending time seeking information is rare.